Representasi Bahasa Ritual Mantra dan Doa Nelayan Bajau: Tinjauan Literatur Review - Ira, Taqdiraa; Ramadiani, Ramadiani (Universitas Negeri Padang, 2025)
Language in traditional societies serves a broader function than mere communication; it acts as a representation of culture, spirituality, and collective identity. This study focuses on ritual language in the form of prayers and mantras used by the Bajau fishing community, a maritime group deeply connected to the sea as the center of their livelihood and belief system. Employing an interdisciplinary approach that integrates anthropological linguistics, semiotics, and maritime cultural studies, this research aims to explore the symbolic and performative representations of language in Bajau ritual practices. A mixed-method approach is applied, with bibliometric data collected through Publish or Perish and analyzed using VOSviewer software. The analysis reveals a growing academic interest in the semantics and symbolism of Bajau prayers and mantras, with a dominant focus on their linguistic-performative function as a medium of communication with supernatural entities. This study underscores the importance of documenting and analyzing ritual language as a means of preserving oral cultural heritage and strengthening local identity amid the pressures of modernization. Keywords: ritual language, Bajau community, mantra, prayer, semiotics, maritime culture